2021
DOI: 10.3390/land11010025
|View full text |Cite
|
Sign up to set email alerts
|

Assemblage Characteristics of Butterflies and Carabid Beetles as a Function of Soil Characteristics and Plant Diversity in Differently Managed Fields, Forests and Ecotones: A Case Study in Tuczno Forest District, Poland

Abstract: A drastic decline in insect fauna on a large scale has been reported. We assume that this is a multifactorial problem involving biotope types and plant diversity, soil characteristics and human activity (management of areas). The aim of our study was to analyze diversity patterns of carabid beetles and butterflies as predatory and phytophagous arthropod groups in response to soil characteristics and plant diversity in different types of ecosystems and ecotones with diverse management situated in a heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…The average abundance in grazed transects was about one-third lower than in mowed transects [68]. In a study carried out by Szyszko-Podgórska [59] on land with different economic uses, it was shown that the number of species did not differ much between mowed and unmowed fallow land.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The average abundance in grazed transects was about one-third lower than in mowed transects [68]. In a study carried out by Szyszko-Podgórska [59] on land with different economic uses, it was shown that the number of species did not differ much between mowed and unmowed fallow land.…”
Section: Discussionmentioning
confidence: 88%
“…In the case of beetles, in the results of this study, it is impossible to conclude which form of use determines the species richness of this taxonomic group of animals. This is probably conditioned by the caught species' characteristics and needs in relation to the environment [59]. On the other hand, an increase in the number of individuals of each species depending on the form of use was observed, with some species showing a clear preference.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ground beetle assemblages have been reported amongst important insect communities from the agricultural landscapes across the globe (Szyszko-Podgórska et al, 2021;Rainio and Niemelä, 2003). Interestingly, most species of carabids were observed with reasonably higher magnitudes from all three study sites except Scarites subterraneus (from Sambrial), Pheropsophus darwini (from Pasrur), Cymindis platicollis (from Sambrial) and Dioryche subrecta (from Sambrial).…”
Section: Discussionmentioning
confidence: 99%
“…Humans, by shaping spatial patterns, can create proper conditions for the occurrence of various animal species. Animals are able to move freely, hence, they can be good indicators of microclimatic conditions created for them [5,6]. Consequently, humans have the potential to influence the occurrence of native animal species, inter alia, by managing spatial patterns in such a way that conditions are fostered for the occurrence of expected species.…”
Section: Introductionmentioning
confidence: 99%